The Effect of Social Media Marketing on Brand Awareness and Purchase Intentionof Vocational School in Tangerang - Ali Maddinsyah; Juhaeri Juhaeri (Journal of Educational Science and Technology (EST), 2021)
This study examines the effect of social media marketing on brand awareness and purchase intention of vocational schools in Tangerang. The object of this research is 178 junior high school students in Tangerang. The method used in this research is quantitative with Structural Equation Modeling (SEM) approach with PLS approach with data processing aids SmrtPLS 3.0 software. Data retrieval using an online questionnaire. The results of this study state that social media marketing has a significant effect on vocational school purchase intentions. Social media marketing through creating vocational school brand awareness. The novelty of this research is a model of social media marketing on brand awareness and purchase intention of vocational school.